Internal Quality Assurance System (Case Study of Model School in State Junior High School Sambas 1 (SMPN 1 Sambas)) - Sri Kurnia; Sukmawati Sukmawati; Muhammad Chiar (STKIP Singkawang, 2019)
The model school is considered to be a great school, even though in reality, the word